The Challenge of Implementing the Marine Ecosystem Service Concept - Townsend, Michael; Davies, Kate; Hanley, Nicholas; Hewitt, Judi E.; Lundquist, Carolyn J.; Lohrer, Andrew M. (Frontiers in Marine Science, 2018)
The concept of ecosystem services has gained traction as a means of linking societal benefits to the underlying ecology and functioning of ecosystems, and is now frequently included in decision-making and legislation. Moving the ecosystem service concept from theory into practice is now crucial. However, advancements in this area of research differ by ecosystem type, and marine systems lag significantly behind terrestrial counterparts in terms of understanding, implementation and number of studies. In this paper we explore several reasons why ecosystem service research has been limited in marine systems and we outline the challenges that hinder progress. Marine systems suffer from a scarcity of spatial data relative to terrestrial counterparts. In terrestrial systems the spatial patterns of land-use/land-cover (LULC) are relatively straightforward to access via satellite and have been used as proxy indicators of service provisions. In contrast, remote sensing tools used to study the surface of the Earth are much less effective at capturing images of the seabed, and by extension marine habitats. Marine waters and their constituents are also frequently driven great distances by winds, tides and currents. This creates a challenge for management as the identification and protection of areas where ecosystem services are exploited is not necessarily sufficient to ensure sustained service delivery. Further complications arise from the three-dimensional uses of marine systems, incorporating activities that use the sea surface, the water column and the benthic habitats below. Progress is being made as technological advancements are resulting in the acquisition of spatial data at faster rates and higher resolutions than previously possible. There is a growing capacity to map, model and value an increasing number of services with initiatives such as InVEST or principle-based modelling. We suggest that awareness is needed around the limited progress in marine systems as this could affect the way we value the biosphere and the relative proportion between biomes.